North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition Position Statement for Telehealth. Issue 5 (27th March 2023) - Franciosi, James P.; Berg, Elizabeth A.; Rosen, John M.; Lee, Jennifer A.; Sandberg, Kelly C.; Srinath, Arvind; Setty, Mala; Li, B U.K.
Abstract : Telehealth (TH) broadly encompasses remote activities of clinical care (telemedicine), provider and patient education, and general health services. The use of synchronous video for TH first occurred in 1964 and then catapulted to the forefront in 2020 during the coronavirus disease 2019 public health emergency. Due to the sudden need for increased TH utilization by nearly all health care providers at that time, TH became essential to clinical practice. However, its sustainable future is unclear in part given that best practices for TH in pediatric gastroenterology (GI), hepatology, and nutrition remain undefined and non-standardized. Key areas for review include historical perspective, general and subspeciality usage, health care disparities, quality of care and the provider-patient interaction, logistics and operations, licensure and liability, reimbursement and insurance coverage, research and quality improvement (QI) priorities, and future use of TH in pediatric GI with a call for advocacy. This position paper from the Telehealth Special Interest Group of North American Society of Gastroenterology, Hepatology and Nutrition provides recommendations for pediatric GI-focused TH best practices, reviews areas for research and QI growth, and presents advocacy opportunities.